Awareness and Factors Affecting the Adoption of E-Mobility Solutions among Tricycle Drivers in Tuguegarao City - Marites Q. Catabay, PhD, Jeremiah Gonzaga, DBM, Ariel F. Melad, PhD (Journal of Daoist Studies, 2026)
The study explores the level of awareness and the factors affecting the adoption of e-mobility solutions among tricycle drivers in Tuguegarao City. The 367 registered tricycle drivers selected at random were the respondents of the study. A structured survey questionnaire was used to gather data on their awareness along six dimensions, namely: electric vehicles, battery technology, charging infrastructure, sustainable mobility, economic opportunities, and policy and regulations. On the other hand, the factors affecting their adoption include acquisition cost, maintenance cost, availability of charging stations, availability of service centers, ease of use, and after-sales support. The findings showed that the tricycle drivers’ awareness of e-mobility solutions was generally low, while all other dimensions were rated “slightly aware.” Among the factors affecting their adoption, acquisition cost, maintenance cost, charging infrastructure, service centers, ease of use, and after-sales support were all rated as significant considerations. Such a result suggests that the lack of knowledge continues to hinder readiness for e-mobility adoption, while drivers still acknowledge the importance of cost, infrastructure, and usability. Similarly, age and sex significantly influence the awareness of e-mobility solutions; male and younger drivers show high awareness. Equally, sex and age significantly influence tricycle drivers’ awareness of e-mobility solutions, with males and younger drivers showing higher awareness, whereas other profile factors are not significant. Adoption decisions are mainly shaped by sex and educational attainment, emphasizing the need for gender-responsive strategies, inclusive training, and stronger structural support to encourage e-mobility transition. Likewise, the study revealed a statistically significant moderate positive relationship between tricycle drivers’ awareness and the factors influencing their decision to adopt e-mobility solutions (r = .533, p = .000). This denotes that increasing drivers’ awareness through education and information campaigns can intensify their readiness and willingness to shift toward sustainable electric mobility. The study recommends the need to strengthen information campaigns, financial support mechanisms, expansion of infrastructure, and training programs to support the transition to sustainable transport.